2001
DOI: 10.17221/6581-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of 2,6-dimethyl-3,5-dialkoxycarbonyl-1,4-dihydropyridines in metal-ion catalyzed lipid peroxidation

Abstract: The 1,4-dihydropyridine (I, 1,4-DHP) derivatives, especially compounds unsubstituted in position 4 (I, R'=H), show AOA in homogenous lipid systems (TIRZITIS et al. 1988;ABDALLA et al. 1999). IThe 2,6-dimethyl-3,5-diethoxycarbonyl-1,4-DHP (trade name Diludin) possesses considerable AOA in the stabilization of edible oils (KOUØIMSKÁ et al. 1993) and exhibits synergistic properties with antioxidants, such as α-tocopherol (TIRZITIS et al. 1983) and 2,6-bis(tert-butyl)-4-hydroxytoluene (BHT) (TIRZITIS & KIRULE 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Therefore, it is widely used as antioxidant in food and for stabilization of edible oils (Kourimska et al. 1993; Tirzitis et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is widely used as antioxidant in food and for stabilization of edible oils (Kourimska et al. 1993; Tirzitis et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ antagonism, IC 50 (mM) Cell SH-SY5Y A7r5 antioxidant activity of the synthesised 1,4-DHP derivatives. Diludine (diethyl-1,4-dihydro-2,6-dimethyl-3,5pyridinecarboxylate), a well-known 1,4-DHP derivative with antioxidant properties [37,38], was used as a positive control. The obtained results ( Fig.…”
Section: Compoundmentioning
confidence: 99%
“…4 (m, 5H). 13 C NMR (CDCl 3 ) d: 14.22; 15.21; 36.38 (N-CH 2 ); 38.52 (4-C-DHP); 60. 21 6.86; N, 3.81; found: C, 71.59; H, 6.90; N, 3.77 2).…”
Section: Synthesismentioning
confidence: 99%
“…Decalpoline is observed to have more potent metal chelating activity than its source extract and BHA (Table 3), which is due to -OH, -O-, and C=O functional groups. In addition, the presence of the 6 CH 3 functional groups may also be responsible for the synergistic effect of decalpoline [21][22][23]. It has been reported that structures containing two or more of the functional groups -OH, -SH, -COOH, -PO 3 H 2 , C=O, -NR 2 , -S-, and -O-in a favorable structurefunction configuration are responsible for their metal chelating activity [24,25].…”
Section: Antioxidant Properties Of Decalpoline (1)mentioning
confidence: 99%